60 million years of glaciation in the Transantarctic Mountains - Barr, Iestyn D.; Spagnolo, Matteo; Rea, Brice R.; Bingham, Robert G.; Oien, Rachel P.; Adamson, Kathryn; Ely, Jeremy C.; Mullan, Donal J.; Pellitero, Ramón; Tomkins, Matt D. (Nature Communications, 2022)
The Antarctic continent reached its current polar location ~83 Ma and became shrouded by ice sheets ~34 Ma, coincident with dramatic global cooling at the Eocene-Oligocene boundary. However, it is not known whether the first Antarctic glaciers formed immediately prior to this or were present significantly earlier. Here we show that mountain glaciers were likely present in the Transantarctic Mountains during the Late Palaeocene (~60–56 Ma) and middle Eocene (~48–40 Ma). Temperate (warm-based) glaciers were prevalent during the Late Eocene (~40–34 Ma) and, in reduced numbers, during the Oligocene (~34–23 Ma), before larger, likely cold-based, ice masses (including ice sheets) dominated. Some temperate mountain glaciers were present during the Miocene Climatic Optimum (~15 Ma), before a widespread switch to cold-based glaciation. Our findings highlight the longevity of glaciation in Antarctica and suggest that glaciers were present even during the Early-Cenozoic greenhouse world.